Identification of a new probiotic strain, Lactiplantibacillus plantarum VHProbi® V38, and its use as an oral health agent - Zhang, Jingyan; Duan, Zhi (Frontiers in Microbiology, 2022)
Introduction Probiotics can be used to treat oral diseases such as dental caries, gingivitis, periodontitis, and halitosis. Methods This study screened for strains capable of inhibiting Streptococcus mutans,one of the primary pathogenic bacteria responsible for dental caries by agar diffusion in different samples. Strain identification was performed by 16S rDNA sequencing and the API 50CH system. The potential functions of the strains in terms of oral health properties were also tested by agglutination assays, growth inhibition assays, adhesion assays, biofilm removal assays and inhibition of adhesion in human primary gingival epithelial (HPGE) cells assays. Results This study identified a probiotic strain from fermented cabbages that has a strong inhibitory effect on Streptococcus mutans. The API 50CH system and 16S rDNA sequencing verified that this was a new strain and it was given the name, Lactiplantibacillus plantarum VHProbi®V38. Agglutination, growth inhibition and adhesion, and biofilm removal tests indicated that L. plantarum VHProbi® V38 inhibited and reduced S. mutans. This probiotic was shown to have a broad antibacterial spectrum, simultaneously inhibiting the growth of periodontal pathogenic bacteria such as Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Fusobacterium nucleatum. After 2 hours of co-cultivation with these pathogens, L. plantarum VHProbi® V38 was able to significantly reduce pathogens adhesion on human primary gingival epithelial (HPGE) cells. Discussion These findings suggest that L. plantarum VHProbi® V38 could potentially prevent and treat periodontal diseases caused by these pathogenic bacteria. L. plantarum VHProbi® V38 also adheres strongly to HPGE cells and thus has potential as an oral probiotic. This study describes new methods that can be used to aid the screening and identification of oral probiotics.